Biomarkers of DNA Damage Response Enable Flow Cytometry-Based Diagnostic to Identify Inborn DNA Repair Defects in Primary Immunodeficiencies - Felgentreff, Kerstin; Baumann, Ulrich; Klemann, Christian; Schuetz, Catharina; Viemann, Dorothee; Wetzke, Martin; Pannicke, Ulrich; Von Hardenberg, Sandra; Auber, Bernd; Debatin, Klaus-Michael; Jacobsen, Eva-Maria; Hoenig, Manfred; et al. (Journal of clinical immunology, 2022)
DNA damage is a constant event in every cell caused by exogenous factors such as ultraviolet and ionizing radiation (UVR/IR) and intercalating drugs, or endogenous metabolic and replicative stress. Proteins of the DNA damage response (DDR) network sense DNA lesions and induce cell cycle arrest, DNA repair, and apoptosis. Genetic defects of DDR or DNA repair proteins can be associated with immunodeficiency, bone marrow failure syndromes, and cancer susceptibility. Although various diagnostic tools are available to evaluate DNA damage, their quality to identify DNA repair deficiencies differs enormously and depends on affected pathways. In this study, we investigated the DDR biomarkers γH2AX (Ser139), p-ATM (Ser1981), and p-CHK2 (Thr68) using flow cytometry on peripheral blood cells obtained from patients with combined immunodeficiencies due to non-homologous end-joining (NHEJ) defects and ataxia telangiectasia (AT) in response to low-dose IR. Significantly reduced induction of all three markers was observed in AT patients compared to controls. However, delayed downregulation of γH2AX was found in patients with NHEJ defects. In contrast to previous reports of DDR in cellular models, these biomarkers were not sensitive enough to identify ARTEMIS deficiency with sufficient reliability. In summary, DDR biomarkers are suitable for diagnosing NHEJ defects and AT, which can be useful in neonates with abnormal TREC levels (T cell receptor excision circles) identified by newborn screening. We conclude that DDR biomarkers have benefits and some limitations depending on the underlying DNA repair deficiency.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Cancer susceptibility; DNA damage response; DNA repair; Immunodeficiency; Radiosensitivity